Surface Defect Segmentation Algorithm of Steel Plate Based on Geometric Median Filter Pruning - Hao, Zhiqiang; Wang, Zhigang; Bai, Dongxu; Tong, Xiliang (Frontiers in bioengineering and biotechnology, 2022)
Problems such as redundancy of detection model parameters make it difficult to apply to factory embedded device applications. This paper focuses on the analysis of different existing deep learning model compression algorithms and proposes a model pruning algorithm based on geometric median filtering for structured pruning and compression of defect segmentation detection networks on the basis of structured pruning. Through experimental comparisons and optimizations, the proposed optimization algorithm can greatly reduce the network parameters and computational effort to achieve effective pruning of the defect detection algorithm for steel plate surfaces.